Pelatihan Pengolahan dan Visualisasi Data Menggunakan Looker Studio untuk Meningkatkan Literasi Digital di Jakarta Islamic Centre - Ruhul Amin; Nita Merlina; Muhammad Haris (Journal Of Computer Science Contributions (JUCOSCO), 2026)
Digital transformation has encouraged community-based organizations to strengthen their capabilities in managing and utilizing data for evidence-based decision-making. However, digital literacy related to data processing and visualization remains limited in many socio-religious organizations. This community service program aimed to enhance the digital literacy and data analytics competencies of youth and mosque members at Jakarta Islamic Centre (JIC) through hands-on training using Looker Studio. The program was implemented through four stages: preparation, training delivery, case-based practical sessions, and evaluation. Twenty participants were involved in interactive lectures, guided practice, and discussions using real organizational data. The evaluation results indicated a high level of participant satisfaction, with an overall mean score of 4.43 out of 5. The highest score was obtained for the perceived benefits of the program (4.64), followed by improvements in participants' skills (4.45) and willingness to participate in future training (4.55). The originality of this program lies in the implementation of an organization-based data analytics training model that integrates real organizational data, data processing, visualization, and interactive dashboard development using Looker Studio. The findings demonstrate that the proposed approach effectively improves participants' digital competencies while promoting a data-driven culture to support monitoring, evaluation, and organizational decision-making. This program can serve as a sustainable model for digital capacity building in community and faith-based organizations.